Nanomaterial, its manufacturing method, and quantum dot light-emitting diode
Patent Information
- Application Number
- JP2022555174
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2020-07-17
- Filing Date
- 2020-12-30
- Publication Date
- 2025-03-05
- Estimated Expiration
- 2040-12-30
AI Technical Summary
【0012】 本発明は、酸化亜鉛ナノ粒子内に他の金属元素をドーピングし、かつ金属酸化物シェルを一層包むことにより、ナノ材料のエネルギーレベルストラクチュアと電子輸送効率を調節することができる。本発明は、ナノ材料全体のエネルギーレベルストラクチュアを調節することにより、量子ドット発光ダイオード中のナノ材料(電子輸送層の材料)を量子ドットのエネルギーレベルに更にマッチングさせ、量子ドット発光層中の電子が電子輸送層に移行することを減少させ、量子ドット発光層中の電子正孔のリコンビネーション効率を向上させ、量子ドット発光ダイオードの効率を大幅に向上させることができる。また、ナノ材料全体の電子輸送の効率を調節することにより、量子ドット発光ダイオードの電子正孔の注入のバランスを確保し、量子ドット発光層の電荷蓄積を減少させ、オージェ再結合を抑制し、電子正孔の放射再結合の効率を向上させ、量子ドット発光ダイオードの効率を大幅に向上させることができる。また、ドーピングされたZnOナノ粒子の表面に一層の酸化物のシェルを包むことにより酸化亜鉛のナノ粒子の安定性を更に向上させ、量子ドット発光ダイオードの安定性を更に向上させ、かつ量子ドット発光ダイオードの寿命を大幅に延長させることができる。
Smart Images

Figure 0007640573000002 
Figure 0007640573000003 
Figure 0007640573000001
Abstract
Description
[Technical field]
[0001] (CROSS-REFERENCE TO RELATED APPLICATIONS) This application claims priority to a Chinese patent application filed with the China Patent Office (equivalent to the Patent Office) on July 17, 2020, bearing application number 202010692288.9 and entitled "Nanomaterial, its manufacturing method, and quantum dot light-emitting diode", and the entire content of that Chinese application is incorporated into this application.
[0002] The present invention relates to the technical field of quantum dot light-emitting devices, and in particular to nanomaterials, their manufacturing methods, and quantum dot light-emitting diodes. [Background technology]
[0003] Quantum dot electroluminescent display technology has the advantages of wavelength tuning, high color saturation, high material stability, and low manufacturing costs, making it a promising candidate for the next generation of display technology. With nearly two decades of technological development, the external quantum efficiency (EQE) of quantum dot light-emitting diodes has improved from 0.01% to more than 20%, and the efficiency of the device, i.e., the efficiency of quantum dot light-emitting diodes (QLEDs), is approaching that of organic light-emitting diodes (OLEDs). Although quantum dot light-emitting diodes have the above advantages, the performance of current quantum dot light-emitting diodes still cannot meet the requirements of industrialization. In particular, blue organic light-emitting diodes cannot meet the requirements of industrialization.
[0004] The current structure of quantum dot light-emitting diodes is similar to that of organic light-emitting diodes, and quantum dot light-emitting diodes also form a sandwich-like pin junction with a hole injection layer, a hole transport layer, a light-emitting layer, an electron transport layer, etc. The light-emitting efficiency is improved by balancing the injection of electrons and the injection of holes. Since the band gap of blue quantum dots is wider than that of red and green quantum dots, electrons and holes cannot be easily injected, and the starting voltage increases and the charge accumulation at the interface increases. This has a significant impact on the life and efficiency of the device (quantum dot light-emitting diode). In particular, charge transfer occurs at the interface between zinc oxide and quantum dots, and since the quantum dots have a lower ability to bind electrons than to bind holes, there is a lot of charge transfer at the interface between zinc oxide and quantum dots. The energy level of the conduction band of blue quantum dots is improved, which makes the charge transfer more intense. The transfer of excited electrons at the interface leads to charge accumulation at the interface, which significantly increases the probability of non-radiative Auger recombination, significantly affecting the efficiency and lifespan of the device. Therefore, the key factors for improving the efficiency and lifespan of the device are to appropriately design the device structure and energy level structure and use materials with good stability.
[0005] When analyzing the structure of the device (quantum dot light emitting diode), the important factors that affect the efficiency and lifespan of the device (quantum dot light emitting diode) are as follows: 1. The energy level difference between the electrode and the hole injection layer or the corrosive effect of the hole injection layer on the electrode, such as the corrosive effect of PEDOT:PSS (Poly 3,4-ethylene dioxythiophene, Polystyrene sulfonate), causes the interface to break down, charges to accumulate, and the injection barrier to increase. 2. The difference in HOMO energy level between the HIL (hole injection layer) and the HTL (hole transport layer), i.e., the barrier height between the HIL and the HTL. 3) The barrier height at the interface between the HTL and the quantum dots and charge accumulation due to the barrier height, such as electron accumulation at the interface between the TFB and the QD, leading to degradation of the TFB and failure of the device. 4. The interaction between the QDs and the ZnO layer includes the energy level difference at the interface between the QDs and the ZnO, the transfer of excitons, and the transfer of electrons. The effect of the above mentioned actions depends on the concentration of oxygen vacancies in the ZnO, the position of the conduction band, and the efficiency of the electron transfer, which changes to some extent with the aging of the storage means of the device. 5. The reaction between ZnO and the cathode, and between ZnO and the cathode metal, results in the formation of metal oxides, which increases the barrier at the interface and increases the concentration of oxygen vacancies in ZnO, thereby increasing the conductivity of ZnO.
[0006] The luminous efficiency of the device (quantum dot light emitting diode) is also an important factor affecting the efficiency of the device, and the monochromaticity and luminous intensity of the device's light can be improved by appropriately designing the optical structure of the device.
[0007] As described above, suitable design of the device structure and energy level structure and the use of stable materials are important factors for improving the efficiency and life span of the device. Summary of the Invention [Problem to be solved by the invention]
[0008] SUMMARY OF THE PRESENT EMBODIMENT The present invention aims to provide a nanomaterial, its manufacturing method and quantum dot light emitting diode to solve the problem of the need to further improve the efficiency and lifetime of conventional devices. [Means for solving the problem]
[0009] In order to solve the problems of the prior art, the present invention provides a nanomaterial having a core-shell structure, the core of the nanomaterial comprises ZnO nanoparticles and a metal element doped into the ZnO nanoparticles, and the shell of the nanomaterial comprises a metal oxide.
[0010] The method for producing the nanomaterial of the present invention includes the steps of adding zinc salt and a salt of a metal element before doping to an alkaline solution and reacting them to obtain ZnO nanoparticles of the doped metal element; and forming a metal oxide shell on the surface of the core by using the ZnO nanoparticles of the doped metal element as a core, thereby obtaining a nanomaterial having a core-shell structure.
[0011] The quantum dot light-emitting diode of the present invention comprises an anode and a cathode attached so as to face each other, a quantum dot light-emitting layer attached between the anode and the cathode, and an electron transport layer attached between the cathode and the quantum dot light-emitting layer, and a material forming the electron transport layer comprises the nanomaterial of the present invention or a nanomaterial produced by the production method of the present invention. Effect of the Invention
[0012] The present invention can adjust the energy level structure and electron transport efficiency of the nanomaterial by doping other metal elements into the zinc oxide nanoparticles and wrapping them with a single layer of metal oxide shell. The present invention can adjust the energy level structure of the entire nanomaterial to further match the nanomaterial (material of the electron transport layer) in the quantum dot light-emitting diode with the energy level of the quantum dot, reduce the transfer of electrons in the quantum dot light-emitting layer to the electron transport layer, improve the recombination efficiency of electrons and holes in the quantum dot light-emitting layer, and greatly improve the efficiency of the quantum dot light-emitting diode. In addition, by adjusting the efficiency of the electron transport of the entire nanomaterial, it is possible to ensure the balance of the injection of electrons and holes in the quantum dot light-emitting diode, reduce the charge accumulation in the quantum dot light-emitting layer, suppress Auger recombination, improve the efficiency of the radiative recombination of electrons and holes, and greatly improve the efficiency of the quantum dot light-emitting diode. In addition, the stability of the zinc oxide nanoparticles can be further improved by wrapping the surface of the doped ZnO nanoparticles with a single layer of oxide shell, and the stability of the quantum dot light-emitting diode can be further improved, and the life of the quantum dot light-emitting diode can be greatly extended. [Brief description of the drawings]
[0013] [Figure 1] 1 is a flow chart showing a method for producing a nanomaterial according to an embodiment of the present invention. [Diagram 2] 1 is a diagram showing the structure of a quantum dot light-emitting diode according to an embodiment of the present invention; DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0014] The present invention provides a nanomaterial, a method for producing the nanomaterial, and quantum dot light emitting diodes. In order to more clearly and in detail describe the objectives, technical matters, and effects of the present invention, the technical matters of the present invention will be described in more detail below. Please note that the following specific examples are provided to illustrate the present invention, but are not intended to limit the present invention.
[0015] In an embodiment of the present invention, a nanomaterial is provided, the nanomaterial having a core-shell structure, the core of the nanomaterial includes ZnO nanoparticles and a metal element doped into the ZnO nanoparticles (hereinafter, referred to as a doping metal element), and the shell of the nanomaterial includes a metal oxide.
[0016] In an embodiment of the present invention, the core of the nanomaterial is a ZnO nanoparticle and a metal element doped into the ZnO nanoparticle, and the shell of the nanomaterial is a metal oxide.
[0017] In the embodiment of the present invention, zinc oxide nanoparticles are improved. Specifically, zinc oxide nanoparticles are doped with other metal elements (such as aluminum, magnesium, lithium, etc.) and are surrounded by a metal oxide shell (such as aluminum oxide, magnesium oxide, lithium oxide, etc.). The conduction band energy levels of the doped metal oxide and the shell metal oxide are both higher than the conduction band energy level of zinc oxide, thereby improving the conduction band energy level of the nanomaterial and matching the conduction band energy level with the energy level structure of various quantum dots, reducing the transfer of electrons in the quantum dot light emitting layer to the electron transport layer, improving the recombination efficiency of electrons and holes in the quantum dot light emitting layer, and greatly improving the efficiency of quantum dot light emitting diodes. When using blue quantum dots, the conduction band energy level of the blue quantum dots is higher (the conduction band energy level of the green quantum dots is higher than the conduction band energy level of the red quantum dots, and the conduction band energy level of the blue quantum dots is higher than the conduction band energy level of the green quantum dots), so it is necessary to improve the conduction band energy level of the zinc oxide nanoparticles, but by using the nanomaterial according to the embodiment of the present invention, it can be matched to the energy level structure of the blue quantum dots.
[0018] In the embodiment of the present invention, various metal elements are doped into zinc oxide nanoparticles, and the doping ratio and thickness of the metal oxide shell are adjusted to adjust the electron transfer rate of the entire nanomaterial, balance the electron and hole injection of the quantum dot light-emitting diode, improve the efficiency of the radiative recombination of electrons and holes, and greatly improve the efficiency of the quantum dot light-emitting diode. When various metal elements are doped, for example, when metal elements such as Mg, Ca, Li, etc. are doped, the band gap of metal oxides such as aluminum oxide, calcium oxide, magnesium oxide, lithium oxide, etc. is very large and the resistance is also very large, so that the conductivity of the zinc oxide nanoparticles may be reduced by doping with Mg, Ca, Li, etc. In the doped metal elements such as Ga, In, they are metal elements of the third main group and have one more electron in valence than Zn, so that they can provide an extra electron. In addition, since the band gap of gallium oxide and indium oxide is small and the conductivity is not good, the conductivity of zinc oxide nanoparticles can be improved by doping with Ga, In, etc. The rate of change of the conductivity can be adjusted by adjusting the doping ratio, and the larger the doping ratio, the more drastic the change in the conductivity. When adjusting the thickness of the metal oxide shell, if the shell material is a metal oxide such as magnesium oxide or aluminum oxide, the thinner the shell thickness, the worse the conductivity of the entire nanomaterial will be due to the high resistance of the metal oxide such as magnesium oxide or aluminum oxide. If the shell material is a metal oxide such as indium oxide, the thinner the shell thickness, the better the conductivity of the entire nanomaterial will be due to the low resistance of the metal oxide such as indium oxide.
[0019] Since quantum dots have a short emission wavelength (red, green and blue quantum dots have short emission wavelengths), the thickness of the shell can be increased by doping the oxide with a metal (such as Mg, Ca, Li, etc.) that has a large band gap or by appropriately increasing the doping ratio, thereby increasing the band gap of zinc oxide, so that the energy level of the band gap can be matched with the energy level of the quantum dots, and the performance of the device can be greatly improved.
[0020] The surface of the zinc oxide nanoparticles is covered with a layer of metal oxide, which can greatly improve the stability of electron transport of the zinc oxide nanoparticles, thereby improving the stability of the quantum dot light-emitting diode and extending the life of the quantum dot light-emitting diode.
[0021] In an embodiment of the present invention, the metal element doped into the ZnO nanoparticles may include one or more of Al, Mg, Li, Ca, Ga, In, etc., but the present invention is not limited thereto.
[0022] In an embodiment of the present invention, the metal element in the metal oxide may include one or more of Al, Mg, Li, Ca, Ga, In, etc., but the present invention is not limited thereto.
[0023] The doping metal element in the ZnO nanoparticles and the metal element in the metal oxide may be selected to be the same material, specifically, the same metal element or different metal elements.
[0024] In an embodiment of the present invention, the doping metal element in the ZnO nanoparticles is similar to the metal element in the metal oxide, which can reduce the lattice mismatch between the shell and the core and improve the stability of the nanomaterial.
[0025] In an embodiment of the present invention, the doping metal element in the ZnO nanoparticles and the metal element in the metal oxide are both Mg or Li. The oxide of Mg or Li has a wider band gap, and the doping of the metal element in the ZnO nanoparticles and the metal oxide shell surrounding the metal element can improve the energy level of the conduction band of the zinc oxide nanoparticles and match the energy level structure of the short-wave quantum dots.
[0026] In an embodiment of the present invention, the molar weight of the doping metal element accounts for 0.5% to 30% of the total molar weight of the doping metal element and zinc element. If the proportion of the doping metal element is too high, the deformation of the lattice of the nanoparticles may increase significantly, and the structural instability may increase significantly.
[0027] In an embodiment of the present invention, the shell has a thickness of 0.5 to 2 nm.
[0028] Referring to FIG. 1, FIG. 1 is a flow chart showing a method for manufacturing a nanomaterial according to an embodiment of the present invention. As shown in FIG. 1, the manufacturing method includes: Step S10 of adding zinc salts, salts of metal elements before doping, to the alkaline solution and reacting to obtain ZnO nanoparticles of doped metal elements; and step S20 of forming a shell of metal oxide on the surface of the ZnO nanoparticles of the doped metal element as a core to obtain a nanomaterial having a core-shell structure.
[0029] The nanomaterial produced by the manufacturing method of the embodiment of the present invention can be the above-mentioned nanomaterial, and the nanomaterial produced by the manufacturing method also has the characteristics and advantages of the above-mentioned nanomaterial, so it will not be described again here.
[0030] In an embodiment of the present invention, the step of obtaining a nanomaterial having a core-shell structure by using the ZnO nanoparticles of the doped metal element as a core and forming a metal oxide shell on the surface of the core may include a step of adding a metal salt to a reaction system of the ZnO nanoparticles of the doped metal element obtained by reaction and reacting the same to form a metal oxide shell on the surface of the ZnO nanoparticles of the doped metal element, thereby obtaining a nanomaterial having a core-shell structure.
[0031] In an embodiment of the present invention, the zinc salt may be a soluble inorganic zinc salt or a soluble organic zinc salt, and may include, but is not limited to, any one or more of zinc acetate, zinc nitrate, zinc chloride, zinc sulfate, and zinc acetate dihydra.
[0032] In an embodiment of the present invention, the alkaline solution can be obtained by dissolving an alkali in an organic solvent. In an embodiment of the present invention, the organic solvent can include one or more of 2-methoxyethanol, carbinol, alcohol, isopropanol, dimethylsulfoxide, etc., but the present invention is not limited thereto.
[0033] In an embodiment of the present invention, the salt of the doping metal element may include one or more of Al salt, Mg salt, Li salt, Ca salt, Ga salt, In salt, etc., but the present invention is not limited thereto.
[0034] In an embodiment of the present invention, the metal element in the metal oxide may include one or more of Al, Mg, Li, Ca, Ga, In, etc., but the present invention is not limited thereto.
[0035] In an embodiment of the present invention, the alkali may include one or more of caustic potash, sodium hydroxide, tetramethylammonium hydroxide, etc., but the present invention is not limited thereto.
[0036] In an embodiment of the present invention, the temperature suitable for the reaction is 20-150° C. Preferably, the temperature suitable for the reaction is 60-90° C.
[0037] In the embodiment of the present invention, the reaction time is 1 to 10 hours. Preferably, the reaction time is 2 to 4 hours.
[0038] In an embodiment of the present invention, a quantum dot light emitting diode is provided, which includes an anode and a cathode attached to face each other, a quantum dot light emitting layer attached between the anode and the cathode, and an electron transport layer attached between the cathode and the quantum dot light emitting layer, and a material forming the electron transport layer can include the nanomaterial or the nanomaterial manufactured by the manufacturing method.
[0039] In an embodiment of the present invention, the material forming the electron transport layer of the quantum dot light-emitting diode may include the nanomaterial according to an embodiment of the present invention or a nanomaterial manufactured by the manufacturing method according to an embodiment of the present invention.
[0040] The quantum dot light emitting diode of this embodiment has various structures, and the quantum dot light emitting diode can be divided into a positive structure and an inverted structure. In this embodiment, a quantum dot light emitting diode with a positive structure shown in FIG. 2 is taken as an example for detailed description. Specifically, as shown in FIG. 2, the quantum dot light emitting diode includes a substrate 1, an anode 2, a hole transport layer 3, a quantum dot light emitting layer 4, an electron transport layer 5, and a cathode 6, which are stacked in a bottom-to-top direction. The material of the electron transport layer 5 is the nanomaterial, the core of the nanomaterial includes ZnO nanoparticles and a metal element doped into the ZnO nanoparticles, and the shell of the nanomaterial includes a metal oxide.
[0041] In an embodiment of the present invention, the thickness of the electron transport layer is 20-60 nm.
[0042] In an embodiment of the present invention, the substrate may be a rigid substrate such as glass or a flexible substrate such as polyethylene terephthalate (PET) or polyimide (PI).
[0043] In an embodiment of the present invention, the anode may include one or more of indium tin oxide (ITO), fluorine-doped tin oxide (FTO), antimony doped tin oxide (ATO), aluminum doped zinc oxide (AZO), etc.
[0044] In the embodiment of the present invention, the hole transport layer may be made of a material having good hole transport properties, such as poly(9,9-dioctylfluorene-co-N-(4-butylphenyl)diphenylamine) (TFB), polyvinyl carbazole (PVK), poly[N,N'-bis(4-butylphenyl)-N,N'-bis(phenyl)-benzi] (Poly-TPD), 4,4'',4''-Tris(carbazol-9-yl)-triphenylamine (TCTA), poly(3,4-ethylenediamine) (Poly ... The organic EL element may include one or more of the following: Poly(3,4-ethylenedioxythiophene)-poly(styrenesulfonate) (PEDOT:PSS), 4,4'-Bis(N-carbazolyl)-1,1'-biphenyl (CBP), NiO, MoO3, etc., but the present invention is not limited thereto.
[0045] In an embodiment of the present invention, the material of the quantum dot light emitting layer is oil-soluble quantum dots, and the oil-soluble quantum dots may include any one or more of binary phase, ternary phase, quaternary phase quantum dots, etc. The binary phase quantum dots may include any one or more of CdS, CdSe, CdTe, InP, AgS, PbS, PbSe, HgS, etc., the ternary phase quantum dots may include any one or more of ZnCdS, CuInS, ZnCdSe, ZnSeS, ZnCdTe, PbSeS, etc., and the quaternary phase quantum dots may include any one or more of ZnCdS / ZnSe, CuInS / ZnS, ZnCdSe / ZnS, CuInSeS, ZnCdTe / ZnS, PbSeS / ZnS, etc. The material of the quantum dot light emitting layer is any one of commonly used red, green, and blue, or yellow, and the quantum dots may or may not contain cadmium. The quantum dot light emitting layer of the material has a wide and continuous excitation spectrum and a highly stable emission spectrum. In this embodiment, the thickness of the quantum dot light emitting layer is about 20-60 nm.
[0046] In an embodiment of the present invention, the cathode may be any one of an aluminum (Al) electrode, a silver (Ag) electrode, a gold (Au) electrode, etc., or any one of a nanoaluminum wire, a nanosilver wire, a nanogold wire, etc. The resistance of the material is small, so that carriers can be easily injected. In this embodiment, the thickness of the cathode is 15 to 30 nm.
[0047] It should be noted that the quantum dot light emitting diode according to the embodiment of the present invention may further include one or more of the following functional layers: a hole injection layer formed between the hole transport layer and the anode, and an electron injection layer formed between the electron transport layer and the cathode.
[0048] In an embodiment of the present invention, a method for manufacturing a quantum dot light emitting diode having a positive structure is further provided, the method including: forming a hole transport layer on a substrate; forming a quantum dot light emitting layer on the hole transport layer; forming an electron transport layer on the quantum dot light emitting layer, the material of the electron transport layer being a nano-material, the core of the nano-material comprising ZnO nano-particles and a metal element doped in the ZnO nano-particles, and the shell of the nano-material comprising a metal oxide; and forming a cathode on the electron transport layer to obtain a quantum dot light emitting diode.
[0049] In this embodiment, in order to obtain a high-quality hole transport layer, the anode needs to be pre-treated, which includes the steps of cleaning the anode with a cleaning agent to initially remove contaminants on the surface of the anode, performing ultrasonic cleaning in deionized water, propanone, absolute ethanol, and deionized water for 20 minutes to remove surface impurities, and blowing off the fluid with high-purity nitrogen to obtain the anode.
[0050] In an embodiment of the present invention, the step of forming a hole transport layer on the substrate includes the steps of: feeding the substrate into a spin processor, and then spin coating the prepared hole transport material solution to form a film; adjusting the thickness of the film by adjusting the concentration of the solution, the spin coating speed and the spin coating time; and forming the hole transport layer by performing thermal annealing at an appropriate temperature.
[0051] In an embodiment of the present invention, the step of forming a quantum dot light-emitting layer on the hole transport layer includes the steps of: feeding the prepared hole transport substrate into a spin processor, and then spin-coating a solution of a light-emitting material having a predetermined concentration to form a film; adjusting the thickness of the quantum dot light-emitting layer by adjusting the concentration of the solution, the spin-coating speed and the spin-coating time; and drying at an appropriate temperature to form the quantum dot light-emitting layer.
[0052] In an embodiment of the present invention, the step of forming an electron transport layer on the quantum dot light emitting layer includes the steps of: feeding the substrate of the manufactured quantum dot light emitting layer into a spin processor, spin coating a solution of an electron transport material having a predetermined concentration to form a film; adjusting the concentration of the solution, the spin coating speed (the rotation speed is 3000-5000 rpm) and the spin coating time to adjust the thickness of the electron transport layer; and forming the electron transport layer by annealing and film formation. When annealing is performed, annealing can be performed in air or nitrogen atmosphere. The operator can select a suitable annealing atmosphere according to actual needs.
[0053] In an embodiment of the present invention, a packaging process is carried out on the manufactured quantum dot light emitting diode. The packaging process can be carried out by a conventional packaging device or manually. In an embodiment of the present invention, when carrying out the packaging process, the oxygen content and water content can be kept below 0.1 ppm to ensure the stability of the device.
[0054] In the present embodiment, a chemical method or a physical method can be used to manufacture each layer. The chemical method can include any one or more of a chemical vapor deposition (CVD), a successive ionic layer adsorption and reaction (SILAR), anodization, an electrolytic deposition, and a coprecipitation method, but the present invention is not limited thereto. The physical method may include any one or more of a solution method (e.g., spin coating method, printing method, knife coating method, dip-coating technique, immersion method, spraying method, roller coating method, casting, slit coating method, strip coating method, etc.), a deposition method (e.g., evaporation method, electron beam evaporation, magnetron sputtering, multi-arc ion plating, etc.), and a precipitation method (e.g., physical vapor deposition, element layer deposition, pulsed laser deposition, etc.), but the present invention is not limited thereto.
[0055] The present invention will now be described in detail with reference to specific examples.
[0056] <Example> 1. Nanomaterials manufacturing (1) 10 mmol of tetramethylammonium hydroxide is added to 30 ml of 2-methoxyethanol, and then heated for 20 minutes using a water-bath heating means. (2) 6 mmol of zinc acetate was added to 2 mmol of aluminum acetate and stirred for 3 hours to obtain a clear solution, producing aluminum-doped zinc oxide nanoparticles. (3) After further adding 2 mmol of aluminum acetate, sonication is carried out for 45 min, and then the sonication is stopped for 5 s every 2 min to encase a shell on the nanoparticles, thereby obtaining nanomaterials with a core-shell structure. (4) Nanomaterials are obtained by washing with ethyl acetate and alcohol, and the obtained nanomaterials are dissolved in an ethanol solution.
[0057] 2. Manufacturing of quantum dot light-emitting diodes (1) The first electrode is formed by evaporating ITO on the substrate. The thickness of the ITO is 40 nm. The surface of the part is cleaned by cleaning with UVO (ultraviolet ozone cleaning equipment) for 15 minutes and the wettability of the surface is ensured. (2) A hole injection layer is formed by spin-coating a layer of PEDOT:PSS on the ITO. The rotation speed of the spin-coating is 5000 r / min. After spin-coating for 40 s, annealing is performed at a temperature of 150° C. for 15 min. Step (2) is performed in air. (3) A hole transport layer is formed by spin-coating a layer of TFB on the PEDOT:PSS. The TFB is dissolved in chlorobenzene at a concentration of 8 mg / ml, and the spin-coating speed is 3000 r / min. After spin-coating for 30 s, the substrate is heated at 150°C for 30 min. Step (3) is carried out in a glove box. (4) A quantum dot light-emitting layer is spin-coated on the TFB. The quantum dots are dissolved in n-octane, and the concentration is 20 mg / ml. The spin-coating speed is 2000 r / min. After spin-coating for 30 s, the layer is heated at 100°C for 20 min. Step (4) is carried out in a glove box. (5) The nanomaterial prepared on the quantum dot light-emitting layer is spin-coated to form an electron transport layer. The nanomaterial is dissolved in alcohol, the concentration of which is 30 mg / ml, and the spin-coating speed is 3000 r / min. After spin-coating for 30 s, the material is heated at a temperature of 100°C for 30 min. Step (5) is carried out in a glove box. (6) A second electrode is formed by evaporating a layer of Al on the electron transport layer, the thickness of the Al electrode being 100 nm.
[0058] <Comparative example> High purity zinc oxide nanoparticles are used in place of the nanomaterials and other steps are left unchanged.
[0059] The quantum dot light emitting diodes of the present invention and the comparative quantum dot light emitting diodes were measured. The measurement results are shown in Table 1.
[0060] Table 1. Efficiency and lifetime of quantum dot light-emitting diodes JPEG0007640573000001.jpg26170
[0061] In Table 1, T95 (1000nit) represents the time it takes for the luminance of the element to decrease from 1000nit to 95%.
[0062] As shown in Table 1, the efficiency and lifespan of the device can be significantly improved by using the nanomaterials according to the embodiments of the present invention. Specifically, the efficiency of the device can be improved to the maximum value under ideal conditions, and the lifespan can be extended by more than two times.
[0063] As described above, the present invention provides a nanomaterial, a manufacturing method thereof, and a quantum dot light-emitting diode in the embodiment of the present invention. In the present invention, the nanomaterial manufactured by the sol-gel method is used as the material of the electron transport layer of the device. In the present invention, the zinc oxide nanoparticles are doped with other metal elements and wrapped with a metal oxide shell, thereby adjusting the energy level structure and electron transport efficiency of the nanomaterial. This can further match the energy levels of the quantum dots and the nanomaterial in the device, reduce the transfer of electrons in the quantum dot light-emitting layer to the electron transport layer, and improve the electron-hole recombination efficiency in the quantum dot light-emitting layer. In addition, it can ensure the balance of electron-hole injection in the device, reduce the charge accumulation in the quantum dot light-emitting layer, suppress Auger recombination, and improve the efficiency of electron-hole radiative recombination. This can ensure the stability of the zinc oxide nanoparticles and improve the stability of the entire device.
[0064] Although a preferred embodiment of the present invention has been described above, the above embodiment is merely illustrative of the present invention, and therefore those skilled in the art may improve or modify the details of the present invention, and such improvements or modifications are of course included in the present invention.
Claims
1. Adding zinc salt and salt of metal element before doping to alkaline solution and reacting to obtain ZnO nanoparticles of doped metal element; The ZnO nanoparticles of the doping metal element are used as a core, and a shell of metal oxide is formed on the surface of the core to obtain a nanomaterial having a core-shell structure; The step of obtaining a nanomaterial having a core-shell structure by forming a metal oxide shell on the surface of the doped metal element ZnO nanoparticles as a core includes the step of adding a metal salt to a reaction system of the doped metal element ZnO nanoparticles obtained by reaction, and reacting the metal salt to form a metal oxide shell on the surface of the doped metal element ZnO nanoparticles as a core, thereby obtaining a nanomaterial having a core-shell structure; The zinc salt includes one or more of zinc acetate, zinc nitrate, zinc chloride, zinc sulfate, and zinc acetate dihydra; The salt of the doping metal element comprises a Li salt, The metal element in the metal oxide includes Li, The alkali in the alkaline solution includes one or more of potassium hydroxide and sodium hydroxide; the doping metal element in the ZnO nanoparticles and the metal element in the metal oxide are the same element, and the doping metal element in the ZnO nanoparticles and the metal element in the metal oxide are both Li; the shell has a thickness of 0.5 to 2 nm; The alkaline solution is obtained by dissolving an alkali in an organic solvent, and the organic solvent is 2-methoxyethanol, carbinol, or isopropanol. A method for producing a nanomaterial, comprising the steps of:
2. 2. The method for producing nanomaterials according to claim 1, wherein the molar amount of the doping metal element accounts for 0.5% to 30% of the total molar amount of the doping metal element and zinc element.
3. The present invention includes a substrate made of polyethylene terephthalate or polyimide, an anode and a cathode mounted to face each other, a quantum dot light emitting layer mounted between the anode and the cathode, a hole transport layer mounted between the anode and the quantum dot light emitting layer, and an electron transport layer mounted between the cathode and the quantum dot light emitting layer, A quantum dot light-emitting diode including, from bottom to top, the substrate, the anode, the hole transport layer, the quantum dot light-emitting layer, the electron transport layer, and the cathode, The material for forming the electron transport layer is A nanomaterial having a core-shell structure, the core of the nanomaterial comprises ZnO nanoparticles and a metal element doped into the ZnO nanoparticles, and the shell of the nanomaterial comprises a metal oxide; the doping metal element in the ZnO nanoparticles and the metal element in the metal oxide are the same element, and the doping metal element in the ZnO nanoparticles and the metal element in the metal oxide are both Li; the shell has a thickness of 0.5 to 2 nm; The molar amount of the doping metal element accounts for 0.5% to 30% of the total molar amount of the doping metal element and the zinc element; The core of the nanomaterial is a ZnO nanoparticle and a metal element doped into the ZnO nanoparticle, and the shell of the nanomaterial is a metal oxide; The thickness of the electron transport layer is 20 to 60 nm. A quantum dot light-emitting diode characterized by:
4. A method for producing a quantum dot light-emitting diode, comprising: a nanomaterial obtaining step of obtaining a nanomaterial having a core-shell structure; and a quantum dot light-emitting diode producing step of producing a quantum dot light-emitting diode using the nanomaterial obtained by the nanomaterial obtaining step, The nanomaterial obtaining step includes: Adding zinc salt and salt of metal element before doping to alkaline solution and reacting to obtain ZnO nanoparticles of doped metal element; The ZnO nanoparticles of the doping metal element are used as a core, and a shell of metal oxide is formed on the surface of the core to obtain a nanomaterial having a core-shell structure; The step of obtaining a nanomaterial having a core-shell structure by forming a metal oxide shell on the surface of the doped metal element ZnO nanoparticles as a core includes the step of adding a metal salt to a reaction system of the doped metal element ZnO nanoparticles obtained by reaction, and reacting the metal salt to form a metal oxide shell on the surface of the doped metal element ZnO nanoparticles as a core, thereby obtaining a nanomaterial having a core-shell structure; The zinc salt includes one or more of zinc acetate, zinc nitrate, zinc chloride, zinc sulfate, and zinc acetate dihydra; The salt of the doping metal element comprises a Li salt, The metal element in the metal oxide includes Li, The alkali in the alkaline solution includes one or more of potassium hydroxide and sodium hydroxide; the doping metal element in the ZnO nanoparticles and the metal element in the metal oxide are the same element, and the doping metal element in the ZnO nanoparticles and the metal element in the metal oxide are both Li; the shell has a thickness of 0.5 to 2 nm; The alkaline solution is obtained by dissolving an alkali in an organic solvent, and the organic solvent is 2-methoxyethanol, carbinol, or isopropanol; The quantum dot light emitting diode manufacturing process includes: forming a hole transport layer on a substrate; forming a quantum dot light emitting layer on the hole transport layer; forming an electron transport layer on the quantum dot light emitting layer using the nanomaterial obtained in the nanomaterial obtaining step; forming a cathode on the electron transport layer to obtain a quantum dot light emitting diode; Before the step of forming a hole transport layer on the substrate, a step of pre-treating the anode is performed; The step of pretreating the anode comprises: initially removing contaminants from the surface of the anode by cleaning the anode with a cleaning agent; removing surface impurities by ultrasonic cleaning in deionized water, propanone, absolute ethanol, or deionized water for 20 minutes; and obtaining an anode by blowing the fluid with high purity nitrogen. A method for producing a quantum dot light-emitting diode comprising the steps of:
Citation Information
Patent Citations
Nanocrystal, nanocrystal composition, light emitting device and method for producing nanocrystal
CN110993808A
Quantum dot light-emitting diodes containing inorganic electron transport layers
JP2008533735A
Mixed ligand surface-modified nanoparticles
JP2011508019A
Quantum dot light emitting diode, manufacturing method thereof, and quantum dot light emitting display device
JP2020061369A
Monodisperse Core / Shell and Other Complex Structured Nanocrystals and Methods of Preparing the Same
US20100308272A1